Strategies for implementation of green roofs in developing countries - Durdyev, Serdar; Koc, Kerim; Karaca, Ferhat; Gurgun, Asli Pelin (EMERALD GROUP PUBLISHING LTD, 2023)
Purpose Reportedly, green roof (GR) makes a significant contribution towards a truly sustainable-built environment; however, its implementation is yet to hit a sufficient level in developing countries. Thus, this study assesses GR implementation strategies in developing countries by providing a comparative analysis through experts in Kazakhstan, Malaysia and Turkey. Design/methodology/approach The study adopts a four-step methodological approach to achieve the research aim: literature review, focus group discussion, fuzzy analytical hierarchy process (FAHP) analysis and correlation analyses. First, a literature review followed by a focus group discussion is used to determine 18 (out of 25 initially) strategies for the selected context and these are classified into three categories: governmental and institutional support, knowledge and information and policy and regulation. Afterward, the identified GR strategies are evaluated using the FAHP with the data gathered from the experts in the countries studied. Finally, correlation analyses were used to observe the strength of agreement between the assessments of experts from the included countries. Findings The findings indicate that financial incentives, low-cost government loans and subsidies and tax rebates are the essential strategies for the wider adoption of GR. Evaluating the policy and regulations strategies also showed that mandatory GR policies and regulations and better enforcement of the developed GR policies are ranked as the most prominent strategies. The findings show a low level of agreement among respondents from Kazakhstan, while there is a high level of agreement between the experts in Malaysia and Turkey. Research limitations/implications The research contribution is twofold. First (research implication), the study identifies the strategies through a complete literature review. Second, the identified strategies are evaluated through the lenses of experts in three developing countries which are hoped to provide (practical contribution) a better understanding of the most effective strategies that require attention and enable the frontline stakeholders (particularly government authorities) to focus on them. Originality/value The study findings provide a good point of departure to explore the strategies for broader adoption of GRs in developing economic setting.
Keywords: Built environment; Developing countries; Green building; Green roofs; SDG9; SDG11; Strategies; Sustainability; Sustainable construction; FUZZY AHP; CONSTRUCTION-INDUSTRY; BARRIERS; BENEFITS; ADOPTION; DRIVERS; Engineering; Business & Economics